Problematizing service-learning : critical reflections for development and action - Stewart, Trae; Webster, Nicole (Emerald Publishing Limited : Information Age Publishing, 2011)
Interest in and research on civic engagement and service-learning have increased exponentially. In this rapid growth, efforts have been made to institutionalize pedagogies of engagement across both K-12 and higher education. As a result, increased positive attention has been complemented equally by well-founded critiques complicating experiential approaches' claims and questioning if institutional, financial, and philosophical commitment is warranted. A key complaint from these critical voices is the tightly woven, protective insular core in the field of service-learning. This claim is not unfounded, nor necessarily bad. Initial efforts to legitimize service-learning and other forms of community-based education required group cohesion. The concern, however, is that the initial group cohesion has led to groupthink wherein group members have avoided critical analysis and evaluation. This book aims to prevent groupthink within the field of service-learning by allowing for the examination of effective alternatives by new voices who can serve as "critical evaluators" from within the field itself. Myriad perspectives are offered, including empirical, theoretical, practical, and community perspectives. Authors challenge preconceived notions of service-learning, who is benefited by this pedagogy, outcomes of participation and implementation, and most importantly the theoretical, conceptual, and methodological lenses through which service-learning is even considered. The book allows servicelearning's major criticisms to be examined, challenges to be voiced, and research agendas to be laid. This book parallels service-learning's presence and popularity across various disciplines/fields. Chapters are written from broad perspectives and are aimed to inform service-learning researchers and educators, community organizations, and policy makers who consider service-learning as a means to address civic responsibility. Authors expose theoretical and philosophical concerns circulating in the field, and often still occupying spaces on the fringe of discourse, action, and research. The book raises fundamental questions for undergraduate and graduate courses with social justice themes by considering the implications that pedagogies of engagement have on learners and communities.